Highly Efficient Modification of Bacterial Artificial Chromosomes (BACs) Using Novel Shuttle Vectors Containing the R6Kγ Origin of Replication - Gong, Shiaoching; Yang, Xiangdong William; Li, Chenjian; Heintz, Nathaniel (Genome Research, 2002)
Bacterial artificial chromosome (BAC) mediated transgenesis has proven to be a highly reliable way to obtain accurate transgene expression for in vivo studies of gene expression and function. A rate-limiting step in use of this technology to characterize large numbers of genes has been the process with which BACs can be modified by homologous recombination in Escherichia coli. We report here a highly efficient method for modifying BACs by using a novel set of shuttle vectors that contain the R6Kγ origin for DNA replication, the E. coli RecA gene for recombination, and the SacBgene for negative selection. These new vectors greatly increased the ease with which one can clone the shuttle vectors, as well as screen for co-integrated and resolved clones. Furthermore, we simplify the shuttle vector cloning to one step by incorporation of a “built-in” resolution cassette for rapid removal of the unwanted vector sequences. This new system has been used to modify a dozen BACs. It is well suited for efficient production of modified BACs for use in a variety of in vivo studies.
10.1101/gr.476202